Molecular characterization of cDNA coding for 33.5 and 41 kDa oocyst and sporocyst proteins that are differentially regulated in different strains of Eimeria maxima - Jenkins, Mark C.; Parker, Carolyn; Jansen, Andrew; Papadopoulos, Marianne Dias; Tucker, Matthew S. (Frontiers in Veterinary Science, 2024)
Eimeria maxima (APU1 and APU2) differ in virulence for chickens, due in part to the greater fecundity of the former. In a previous study, RNA-seq was used to identify a transcripts upregulated in E. maxima APU1 compared to E. maxima APU2. In this study, 2 of these upregulated genes (EMWEY 23530 and EMWEY 48910) were characterized by first confirming upregulation using quantitative RT-PCR. For both EMWEY 23530 and EMWEY 48910, RNA transcription was fairly consistent during sporulation. The extent of differential expression was about 2-fold log2 higher in APU-1 compared to APU-2 (peaking at 18 h for EMWEY 23530 and 0 h for EMWEY 48910). EMWEY 23530 and EMWEY 48910 cDNA were cloned and expressed as polyHis-fusion proteins in Escherichia coli. The observed size of recombinant EMWEY 23530 was 24 kDa; the observed size of recombinant EMWEY 48910 was 35 kDa, which are consistent with the predicted size based on the coding sequences. Immunostaining 2D gel blots of E. maxima APU1 and APU2 oocyst/sporocyst protein with antisera specific for EMWEY 23530 identified a 33.5 kDa protein with a pH 7.4 isoelectric point (Emax p33.5). Similar 2D gel blot analysis with EMWEY 48910 identified a 41 kDa protein with a pH 7.2 isoelectric point (Emax p41). The intensity of Emax p33.5 and Emax p41 was noticeably greater in oocyst/sporocyst proteins from E. maxima APU1 compared to E. maxima APU2. This was corroborated by ELISA wherein equal amounts of total E. maxima APU1 and APU2 protein were probed with serial dilutions of anti-rEmax p33.5 or anti-rEmax p41. Immunofluorescence (IFA) staining of permeabilized unsporulated E. maxima APU1 and APU2 oocysts revealed Emax p33.5 to be localized in one end of oocysts, while Emax p41 appeared on the surface of oocysts. After sporulation, the p33.5 and p41 antigens appeared loosely associated with sporocysts. Taken together, these data confirm excess expression of two proteins in the E. maxima strain characterized by greater fecundity and virulence, and may provide insight into basis for phenotypic differences among different E. maxima.